Analisis Analisis Kebutuhan Pengembangan Media Pembelajaran Interaktif H5P untuk Mendukung Literasi Numerasi Bilangan di Kelas V SD - Waliah, Diyah Rutin; Rufiana, Intan Sari; Hidayanto, Erry (Media Pendidikan Matematika, 2026)
The low numeracy literacy of elementary school students, particularly in number, remains a major problem, as reflected in the 2024 PISA (Philosophy of Mathematics and Natural Sciences) achievement, which is below the international average. Students tend to have difficulty understanding number concepts, interpreting data, and applying mathematical knowledge in real-life contexts. This study aims to analyze the need for developing H5P-based interactive learning media to improve the numeracy literacy of fifth-grade elementary school students. The study used a qualitative descriptive approach through needs analysis, involving 56 students and 8 elementary school teachers. Data collection techniques included numeracy literacy tests and questionnaires. The results showed that 84.3% of students experienced difficulty in solving contextual story problems, while only 48.18% of students were able to achieve numeracy reasoning skills. On the other hand, 86.4% of students expressed a high preference for interactive learning media such as videos, quizzes, and simulations, and 79.6% of students felt helped in understanding the material through these media. Teachers also expressed the need for media that could provide direct feedback and monitor student learning progress in real time. These findings demonstrate a strong need for the development of interactive, contextual, and adaptive H5P-based learning media. Therefore, it can be concluded that interactive learning media is needed by students and teachers to address low numeracy literacy. Thus, the development of H5P media has the potential to increase student engagement, motivation, and understanding in numeracy literacy, making it a suitable innovative solution for mathematics learning in elementary schools